2023
DOI: 10.1039/d2ra07440k
|View full text |Cite
|
Sign up to set email alerts
|

Refined definition of the critical micelle concentration and application to alkyl maltosides used in membrane protein research

Abstract: A refined definition of the critical micelle concentration is connected to fluorescence methods and applied to test a molecular thermodynamic model of nonionic detergents used for in vitro studies of membrane proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…More similar to detergents are n-alkyl alcohols with the number of carbon atoms between 1 and 5, which were investigated in aqueous biphasic systems composed of PEG and salts (Willauer et al 2002). The authors characterized the partitioning of the alcohols between the two phases by the transfer free energy of a methylene group, ΔG CH 2 , a ( ) measure of solution polarity, which is similar to the strategy employed in molecular thermodynamic modeling of g mic (Nagarajan andRuckenstein 1991h et al 2015;Bothe et al 2023). Willauer et al (2002) found a linear correlation between ΔG CH 2 and the difference in c OE between the two phases that is independent of the relative molecular weight (in this case, PEG1000, PEG2000, and PEG3400 were investigated).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More similar to detergents are n-alkyl alcohols with the number of carbon atoms between 1 and 5, which were investigated in aqueous biphasic systems composed of PEG and salts (Willauer et al 2002). The authors characterized the partitioning of the alcohols between the two phases by the transfer free energy of a methylene group, ΔG CH 2 , a ( ) measure of solution polarity, which is similar to the strategy employed in molecular thermodynamic modeling of g mic (Nagarajan andRuckenstein 1991h et al 2015;Bothe et al 2023). Willauer et al (2002) found a linear correlation between ΔG CH 2 and the difference in c OE between the two phases that is independent of the relative molecular weight (in this case, PEG1000, PEG2000, and PEG3400 were investigated).…”
Section: Discussionmentioning
confidence: 99%
“…( 27) is too complicated for practical use. However, Bothe et al (2023) found that for large m, x ≈ y at the breaking point corresponding to the traditional de nition of the CMC. This result also follows from Eq.…”
Section: Note Thatmentioning
confidence: 98%
See 3 more Smart Citations